2009
DOI: 10.1021/jp8085446
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Exchange Bias in γ-Fe2O3/CoO and Reverse CoO/γ-Fe2O3 Binary Nanoparticles

Abstract: γ-Fe2O3/CoO and reverse CoO/γ-Fe2O3 binary nanoparticles have been prepared by a facile, two-step chemical route through the thermal decomposition of Co(acac)2 and Fe(acac)3 in hot oleyl amine. The synthesis is based on heterogeneous nucleation and growth of the second component on seed nanoparticles of the first one. The binary particles have been characterized by X-ray diffraction, transmission electron microscopy, and cognate techniques. The heteroparticles are very stable in nonpolar organic solvents due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Exchange bias has been observed in different types of iron oxide-based core/shell nanoparticles, such as Fe/γ-Fe 2 O 3 [27,28,29], Fe/Fe 3 O 4 [30,31], FeO/Fe 3 O 4 [32,33,34], Fe 3 O 4 /γ-Fe 2 O 3 [35], γ-Fe 2 O 3 /CoO [36], MnFe 2 O 4 /γ-Fe 2 O 3 , and CoFe 2 O 4 /γ-Fe 2 O 3 [73]. The EB effect has been mainly associated with exchange anisotropy originating from exchange coupling between the shell and the core.…”
Section: Exchange Bias Effect In Core/shell Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Exchange bias has been observed in different types of iron oxide-based core/shell nanoparticles, such as Fe/γ-Fe 2 O 3 [27,28,29], Fe/Fe 3 O 4 [30,31], FeO/Fe 3 O 4 [32,33,34], Fe 3 O 4 /γ-Fe 2 O 3 [35], γ-Fe 2 O 3 /CoO [36], MnFe 2 O 4 /γ-Fe 2 O 3 , and CoFe 2 O 4 /γ-Fe 2 O 3 [73]. The EB effect has been mainly associated with exchange anisotropy originating from exchange coupling between the shell and the core.…”
Section: Exchange Bias Effect In Core/shell Nanoparticlesmentioning
confidence: 99%
“…The magnetic properties of the core/shell MNPs are dependent both on the core and the shell size, shape, composition, interface roughness, etc. [27,28,29,30,31,32,33,34,35,36,73,74,75,76]. These parameters can be easily tuned during the synthesis process and a rich variety of magnetic core/shell systems can be produced by a proper choice of the materials and dimensions of both the core and the shell.…”
Section: Exchange Bias Effect In Core/shell Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 1956 EB was observed in many core-shell nanoparticles with T C >T N (Cure Temperature of FM is higher than Néel's Temperature of AF [6]. In recent studies it was found that exchange coupling in AF/FiM nanoparticles strongly depends on the core size, the shell thickness and the shape or crystal quality [7,8].…”
Section: Introductionmentioning
confidence: 99%